The Evolution of Project Management Offices (PMOs) Toward xMO Models in Organisations in Qatar - Radi, Ayman; Radi, Aref (Journal of Project Management Research, 2026)
The Project Management Office has evolved from a function focused on project control, reporting, and compliance into a governance structure supporting strategic execution and organizational performance. This evolution has led to the emergence of extended PMO configuration, commonly referred to as xMO, which integrates portfolio governance, value management, and transformation leadership. Despite increasing recognition of xMOs in the literature, empirical evidence from the Middle East remains limited. This study examines the evolution of PMOs toward xMO models within project-based organizations in the State of Qatar. It assesses PMO maturity, explores factors influencing transformation, and evaluates relationships with organizational outcomes, including strategic alignment, governance effectiveness, and agility. The data reflect Qatar-based organizational environments and the perspectives of a diverse professional workforce typical of the sector.